Editorial - Fregonezi, Guilherme Augusto Freitas; Dornelas de Andrade, Armele de Fátima; Britto, Raquel Rodrigues; Bruno, Selma (Journal of Respiratory and CardioVascular Physical Therapy, 2012)
Editorial